SOME ISSUES ON THE ASSESSMENT OF THE VALUE OF PROVISIONS AND CONTINGENT LIABILITIES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This paper examines pricing differences regarding contingencies presented in statements of financial position or notes, which are considered an area for creative accounting. The most important conclusion is that market participants in both countries follow different patterns when incorporating information about provisions and contingent liabilities. More precisely, our results suggest that provisions are value relevant. Contingent liabilities seem to have no value relevance.